Inquiring Pre-service Teachers’ Narratives on Language Policy and Identity during their Practicum (2020)
ABSTRACT: This narrative inquiry aims to unveil the incorporation of policy agency within the construction of teacher identity of pre-service teachers in their academic practicums. Drawing on a critical-sociocultural approach to narrative inquiry, language policy, and teacher identity, the narratives of five students of an English teaching program in Medellín, Colombia, were examined. Their reflections and decision making on foreign language policies regulating their pedagogical practices at various schools show their social and critical awareness. Teaching represents a high moral load for them as they embrace a humanistic perspective. However, their narratives also pose challenges to language teaching programs in helping pre-service teachers to build micropolitical agency supported on solid theoretical knowledge to participate in policymaking. On the one hand, their narrations of the policy appropriation process they undertook show their frustration and disappointment in trying to participate when policy structures and other policy arbiters were close to them. On the other hand, when policy structures and arbiters openly allowed their policy participation, their actions and reflections focused on methodological concerns but rarely addressed social or critical awareness regarding curriculum design and development. Therefore, supporting pre-service teachers in strengthening their identities with solid theoretical constructs should be a priority because they will build micropolitical agency to overcome political tensions and negotiate their policy participation.